The influence of physical exercise on emotional management ability in college students: A serial mediation model of exercise adherence and psychological resilience - Yu-Han Li; Wei-dong Zhu; Hu Lou; Bo Li; Shan-shan Han; Yu-yan Qian (PLoS ONE, 2025)
Objective This study aimed to examine the influence of physical exercise (PE) on emotional management ability (EMA) among college students and to investigate the mediating roles of exercise adherence (EA) and psychological resilience (PR) in the relationship between PE and EMA. Method Demographic information was collected using stratified, cluster, and multi-stage sampling methods. Data on PE, EA, PR, and EMA were collected from college students via the Wenjuanxing platform, resulting in a final sample of 11,388 valid questionnaires. Results Significant positive correlations were found between PE and EMA (r = 0.164, P < 0.01), PE and EA (r = 0.452, P < 0.01), and PE and PR (r = 0.201, P < 0.01). Significant positive correlations were also observed between EA and PR (r = 0.329, P < 0.01), and EA and EMA (r = 0.478, P < 0.01). PR was significantly positively correlated with EMA (r = 0.411, P < 0.01). PE significantly negatively predicted EMA (β = −0.009, P < 0.001). EA mediated the relationship between PE and EMA (95% CI: [0.039, 0.045]). PR also mediated the relationship between PE and EMA (95% CI: [0.001, 0.004]). A serial mediation effect of EA and PR was found in the relationship between PE and EMA (95% CI: [0.008, 0.010]). Conclusion This study reveals the impact of PE, EA, and PR on EMA. The findings suggest that enhancing PE participation, improving EA, and increasing PR can improve EMA among college students.